Early cervical cancer screening: The influence of culture and religion - Fungai Gutusa; Lizeth Roets (AOSIS, 2023)
Background: Screening for cervical cancer at an early stage is essential for providing women with a better chance of receiving effective treatment for both precancers and cancer. Delaying screening until cancer has advanced can be detrimental, resulting in late presentation of cervical cancer and, as a result, cancer metastasis. Aim: The purpose of this study was to assess the extent to which culture and religion influence early cervical cancer screening in women. Setting: The research was conducted in one of the rural districts in Manicaland Province of Zimbabwe. Methods: A qualitative exploratory and contextual design was utilised, and data were gathered by means of semistructured interviews. At 17 semistructured interviews, data saturation was reached and further data collection terminated. Data were thematically analysed. Results: Five themes that described participants' perceptions on culture and religion as barriers to early cervical cancer screening emerged from the data. These included a lack of knowledge, stigmatisation, cultural beliefs and values, religion and a lack of resources. These all negatively affected participants' motivation to seek early screening services. Conclusion: According to the study findings, culture and religion constitute impediments to early cervical cancer screening for rural women. Interventions that encourage screening, such as targeted health education and health promotion materials, must consider cultural and religious views if behaviour change in diverse groups is to be accomplished. Contribution: The study has the potential to inform Zimbabwean health policy and contribute to prospective interventions or health education that encourage women to attend early cancer screening.